Developing Grammar in Context : intermediate with answers - Nettle, Mark; Hopkins, Diana (Cambridge University Press, 2003)
This book provides 50 units of clear explanations and lively practice focusing on key grammar areas. Using real spoken and written examples drawn from the Cambridge International Corpus, this book will help learners consolidate and deepen their understanding of how English works.